Sharks and their relatives: can their past help predict their future? - Hasenei, Aaron; Donelson, Jennifer M.; Ravasi, Timothy; Rummer, Jodie L. (Frontiers in Marine Science, 2023)
Elasmobranchs fishes (i.e., sharks, skates, and rays) have survived five mass extinction events and changed relatively little throughout their 450-million-year evolutionary history. and Ttherefore, elasmobranchs may provide critical evolutionary perspectives on how species and populations may can elicit phenotypic plasticity and adaptation responses to climate change. Unfortunately, despite their roles as critical apex-and meso-predators, most elasmobranch species are considered to be highly vulnerable to the impacts of fisheries exploitation and climate change, which is compounded by their K-selected life history strategies. Furthermore, the future of elasmobranchs fishes is uncertain at best in the face of anthropogenic climate change because there have only been a handful of studies that have directly investigated the effects of climate change related stressors on elasmobranchs. The importance of pPhenotypic plasticity in response to climate change, specifically ocean warming, may be a species' best chance of resilience given the expedited rate of environmental change. However, despite the numerous studies that have investigatedextensive research on plasticity within and across generations for in teleost fishes, there remainsis a lack of knowledge gap for elasmobranch species, owing to their extended life spansprolonged life histories and time to reachdelayed sexual maturity. Here, we present four case studies on different elasmobranch species to lend perspectives on capacities the capacity for phenotypic plasticity within the context of ocean warming. Further, we discuss potential research avenues and modern technologies that may enable future investigations to empirically explore the capacity for phenotypic plasticity responses within in elasmobranchs.